The MusiQual treatment manual for music therapy in a palliative care inpatient setting. (May 2019) - Kirkwood, Jenny; Graham-Wisener, Lisa; McConnell, Tracey; Porter, Sam; Reid, Joanne; Craig, Naomi; Dunlop, Conall; Gordon, Catherine; Thomas, Daniel; Godsal, Jo; Vorster, Aisling
This article presents the treatment manual developed during the MusiQual feasibility study carried out in Belfast by Queen's University Belfast, Every Day Harmony Music Therapy, and Marie Curie Northern Ireland. The MusiQual study considered the feasibility of a multicentre randomised trial to evaluate the effectiveness of music therapy in improving the quality of life of hospice inpatients (protocol: McConnell et al. results: Porter et al.). The procedures in the manual are based fully on those implemented by the Music Therapists during the feasibility study, and it also incorporates the theoretical model defined and published following the realist review of the literature (McConnell and Porter). The manual is presented in the format in which it would be used in the potential future phase III multicentre randomised control trial. It represents a flexible approach to provide enough scope for practicing therapists to adapt their interventions to individual clients as is best practice in music therapy. It aims to provide stable guidelines both to ensure treatment fidelity in a future trial of music therapy for palliative care inpatients and to act as a relevant guide for Music Therapists practicing in this field.